Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Pada Materi Pengklasifikasian Ikan - Yulia Anita; Saleh Hidayat; Haryadi Haryadi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
This article aimed to determine the practicality, validity, and test the effectiveness of material inquiry-based education. The research development procedure basically consists of two main objectives, namely: (1) develop products and (2) test the effectiveness of products in achieving goals. The results showed that the way to develop inquiry-based learning models reviewed the source supporting fish classification material, made the initial draft LKPD, do expert validation and revision, small-scale trials and large-scale trials. Based on the validity test, the developed LKPD was very valid category with an average value of 84.6 all aspects of the assessment. Students also gave a positive response to LKPD with was developed with an of 84.7. This indicated that the valid LKPD was used in the learning process. The effectiveness of LKPD has increased the achievement of student learning outcomes with the presentation of the pretest-posttest value gaining a value of 63.64%. The results of the research obtained be concluded that the LKPD developed meets the medium category, so that it was practical, valid and effective to use. Key words: The Development of LKPD, Inqury-Based Education, The Effectiveness of LKPD